The vital importance of field trips in the further development of biology education - Sodikova K.A (Genius Journals, 2023)
Field trips play an important role in biology education, providing students with opportunities to interact with the natural world in a hands-on and immersive manner. In this article, we explore the importance of field trips in the study of biology, highlighting the various benefits they bring to the learning experience.
Keywords: Excursion; Pupil ecosystems; studied concept; environment